Comparative Genomics Used to Predict Virulence Factors and Metabolic Genes among Monilinia Species - Marina Marcet-Houben; Maria Villarino; Laura Vilanova; Antonieta De Cal; Jan A. L. van Kan; Josep Usall; Toni Gabaldón; Rosario Torres (Journal of Fungi, 2021)
Brown rot, caused by Monilinia spp., is among the most important diseases in stone fruits, and some pome fruits (mainly apples). This disease is responsible for significant yield losses, particularly in stone fruits, when weather conditions favorable for disease development appear. To achieve future sustainable strategies to control brown rot on fruit, one potential approach will be to characterize genomic variation among Monilinia spp. to define, among others, the capacity to infect fruit in this genus. In the present work, we performed genomic and phylogenomic comparisons of five Monilinia species and inferred differences in numbers of secreted proteins, including CAZy proteins and other proteins important for virulence. Duplications specific to Monilinia were sparse and, overall, more genes have been lost than gained. Among Monilinia spp., low variability in the CAZome was observed. Interestingly, we identified several secondary metabolism clusters based on similarity to known clusters, and among them was a cluster with homology to pyriculol that could be responsible for the synthesis of chloromonilicin. Furthermore, we compared sequences of all strains available from NCBI of these species to assess their MAT loci and heterokaryon compatibility systems. Our comparative analyses provide the basis for future studies into understanding how these genomic differences underlie common or differential abilities to interact with the host plant.